The Correlation Of The Al-Quran's Proof Of The Tuban's Special Legen Or Paper Drink In The Perspective Of Chemical Science - Laili, Dhiya Hasna (Universitas Negeri Padang, 2024)
This research discusses about forbidden foods in an Islamic religious perspective, with a focus on typical foods in Indonesia. Food is a basic necessity for human life and has an impact on body health and daily activities. Islam has the concept of halal and thayyib in consuming food, which requires food to be obtained properly and does not harm health. The verses in the Qur'an explain the prohibition against consuming foods such as carrion, blood, pork, and the flesh of animals that are not slaughtered in the name of Allah. This prohibition has a scientific basis and shows that unclean food can have a major impact on the metabolism of the body's metabolism. Recent research has also shown the negative impact of unclean foods and drinks on human growth. Besides that, this research also explains about lelgeln, a traditional Indonesian drink, which is made from siwalan sap. Lelgeln has a sweet taste and good quality if it is rounded without any mixture of non-halal ingredients. However, if the round-up process is not in accordance with religious law, the law can turn into a lawful that contains alcohol and is forbidden in Islam. Therefore, this research provides an understanding of the importance of following the principles of halal food in everyday life.